2015
DOI: 10.1007/s10545-015-9865-1
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial glucose uptake in patients with the m.3243A > G mutation in mitochondrial DNA

Abstract: Mitochondrial mutations impair glucose oxidation and increase glucose uptake in cell cultures and lead to cardiomyopathy in patients. Here we characterize cardiac glucose uptake in 14 patients with the m.3243A > G mutation in mitochondrial DNA. The 14 patients with m.3243A > G and 13 controls were similar in age, physical activity and body mass index. Ten patients had diabetes. Left ventricular glucose uptake per tissue mass (LVGU) was measured with 2-[(18) F]fluoro-2-deoxyglucose positron emission tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…13,14 The available evidence shows similar diagnostic yield of CMRI in comparison with echo; however, the data are very heterogeneous and from a limited number of patients. In studies including m.3243A>G and/or MELAS patients, 2 studies 15,16 reported no CMRI abnormalities, and 1 study 17 reported CMRI abnormalities in nearly all patients. This discrepancy can hopefully be addressed in future research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 The available evidence shows similar diagnostic yield of CMRI in comparison with echo; however, the data are very heterogeneous and from a limited number of patients. In studies including m.3243A>G and/or MELAS patients, 2 studies 15,16 reported no CMRI abnormalities, and 1 study 17 reported CMRI abnormalities in nearly all patients. This discrepancy can hopefully be addressed in future research.…”
Section: Discussionmentioning
confidence: 99%
“…One study of CMRI in 14 participants showed no structural abnormalities, but an overall reduction of myocardial glucose uptake, which may be a biomarker of interest for future study. 16 Only a single study included CMRI data from a pediatric participant. 10 Overall, CMRI has thus far had very limited study in MM, and further investigation will be required to understand the advantages and limitations of this modality in patients with MM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty acid oxidation provides reducing equivalents directly to the mitochondrial respiratory chain, as well as acetyl-CoA for the Krebs cycle, which in turn generates additional reducing equivalents to maintain energy homeostasis. In an otherwise normal heart, the respiratory chain is compromised in cardiac failure, leading to an increase in the NADH/NAD + ratio and a decrease in pyruvate oxidation for gluconeogenesis [26]. This metabolic state decreases the utility of glucose as a backup energy source in the failing heart.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated lactate level in the m.3243A>G was an expected finding and could be a contributing cause of the insulin resistance as fasting lactate levels have been shown to be inversely correlated with glucose uptake in the left ventricle of the heart during an euglycemic hyperinsulinemic clamp in m.3243A>G carriers (39).…”
Section: Discussionmentioning
confidence: 96%